STUDY KOMPARASI LOST FOAM DAN KONVENSIONAL CASTING PRODUK DISC BRAKE - Sumeru Yoso; Suyitno - (ASEAN Journal of Systems Engineering, 2014)
Disc brake component is a vital component with gray cast iron base material, it’s also fast lasting wearing part, so it has be replaced often. The disc brake replacement component in a local market is being supplied by the small scale local metal casting industries have the same quality as the genuine part.Disc brake making process is utilizing casting method inserting RCS core between drag and coup, than metal molten poured inside mold. The problem of this method is the product result often have gas defect because the gas that occur from the mold in casting process cannot be released perfectly, and then trapped in the metal molten caused by permeability or the gas flow in the green sand mold is not good enough.Ventilating disc brake making is not utilizing evaporative casting method or lost foam casting yet at the moment so it need to be research for the gains and the losses between the casting result using conventional method and lost foam casting method, considering that there’s no research for the disc brake component yet as far.This research will give many benefits to know that the thin Styrofoam pattern construction’s of the disc brake, with quit complicated ventilation would not be strong enough to sustain the dry sand mold on the pattern so it will be collapse earlier before the metal molten filled the cavity from the pattern, but it will make good result if it’s combined with the RCS core using. The time duration of the dry sand mold and the re-using will be faster than the conventional casting which using 2 underside mold or drag and upside mold or coup using the green sand.